Impact of maxillomandibular advancement on oral health related quality of life in patients with obstructive sleep apnea: A longitudinal study of the oral health impact profile (OHIP-14) - Misha L. Tan; Jean-Pierre T.F. Ho; Jacco G.C. Tuk; Jan de Lange; Jerôme A.H. Lindeboom (Advances in Oral and Maxillofacial Surgery, 2023)
Background: The aim of this study was to evaluate the impact of maxillomandibular advancement (MMA) on oral health-related quality of life (OHRQoL) in obstructive sleep apnea (OSA) patients prior to, immediately after, and up to 1 year after surgery. Methods: In this prospective study, OHRQoL was measured with the use of the Dutch version of the Oral Health Impact Profile questionnaire (OHIP-14NL). A total of 19 patients were asked to complete the questionnaires prior to surgery (T0), on the first 7 days post-surgery (T1-T7), and 1 month (T8), 6 months (T9), and at least 1 year post surgery (T10). The baseline OHIP score was compared with the post-surgery scores using the Wilcoxon signed-rank test with Bonferroni correction (significance at P < .005). Results: Compared with the baseline, the OHIP score significantly increased in the first month after MMA. At 6 months (T9) and 1 year (T10), the OHIP score decreased compared relative to scores in the immediate postoperative period (T1-T8). However, there was no significant difference found in comparison with the baseline (T0). Conclusion: This study indicates that in OSA patients who undergo MMA, OHRQoL deteriorates in the immediate postoperative period. However, at 6 months to 1 year post surgery, OHRQoL does not significantly differ from its baseline value prior to MMA.